2019
DOI: 10.1001/jamanetworkopen.2019.9966
|View full text |Cite
|
Sign up to set email alerts
|

Association of Restless Legs Syndrome With Risk of Suicide and Self-harm

Abstract: Key Points Questions Is restless legs syndrome associated with a high risk of suicide and self-harm? Findings In a cohort study that included 169 373 participants, individuals with restless legs syndrome had a higher risk of suicide and self-harm compared with age- and sex-matched participants without restless legs syndrome, and the increased risk was independent of common diseases and conditions. Meaning Restless legs syndrome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Our study findings agree in part with earlier studies (Ahmedani et al ., 2017; Wei and Mukamal, 2019; Zhuang et al ., 2019) which demonstrated an association between the number of physical health problems and suicide risk, though we extended this by considering another dimension of physical health, activity limitation, which was absent in these studies. Our findings that the number of physical conditions is no longer associated with suicide risk after adjustment for the effect that they have on activities of daily living are in agreement with a population-based study conducted in the USA (Kaplan et al ., 2007) though the authors did not consider variation by the degree of activity limitation and age group.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our study findings agree in part with earlier studies (Ahmedani et al ., 2017; Wei and Mukamal, 2019; Zhuang et al ., 2019) which demonstrated an association between the number of physical health problems and suicide risk, though we extended this by considering another dimension of physical health, activity limitation, which was absent in these studies. Our findings that the number of physical conditions is no longer associated with suicide risk after adjustment for the effect that they have on activities of daily living are in agreement with a population-based study conducted in the USA (Kaplan et al ., 2007) though the authors did not consider variation by the degree of activity limitation and age group.…”
Section: Discussionmentioning
confidence: 96%
“…Drawing upon the interpersonal theory of suicide, heightened feelings of burdensomeness, loneliness and social isolation among individuals with a disability could spiral to depression and trigger suicidal thoughts and attempts (Khazem, 2018). People with disabling conditions tend to have sleep disturbances (Kinne et al, 2004;Shandra et al, 2014) and findings from a systematic review revealed that sleep disturbances are independent risk factors for suicide (Bernert et al, 2015) This, however, might not be true in all situationsa large-scale study of 169 373 individuals in the USA found an association between physical health problem (restless leg syndrome) and suicide risk even after adjusting for the effect of sleep disturbance, depression and other covariates (Zhuang et al, 2019). Counter to expectations, there was no indication that activity limitation or multimorbidity was associated with increased suicide risk at older ages.…”
Section: Possible Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…SLE is known to influence human behavior in multiple ways, often increasing the risk of suicide and depression [34][35][36]. In a study involving 169,373 participants, idiopathic RLS was found to be linked to an elevated risk of suicide and self-harm [37]. However, the mechanisms underlying the link between RLS and SLE, suicide, or self-harm remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The sleep disruptions that occur may be responsible for daytime sleepiness, fatigue [1,8,9], and impaired performance during activities of daily living [10]. Finally, an association between RLS and a high risk of suicide and self-harm, independent of comorbidities and conditions, has been recently reported [11].…”
Section: Introductionmentioning
confidence: 99%